Influenza vaccination is safe and effective in patients suffering from fibromyalgia syndrome - J. N. Ablin; V. Aloush; A. Brill; M. Berman; M. Barzilai; D. Caspi; M. Mandelboim; D. Levartovsky; A. Polachek; Y. Wolman; D. Paran; M. Barkagan; et al. (PAGEPress Publications, 2015)
The fibromyalgia syndrome (FMS) is considered to result from the exposure of a genetically susceptible individual to various triggers, such as physical trauma, stress, viral infections etc. A possible role of vaccination in FMS etiology has been suspected. Our objective was to evaluate the efficacy and safety of influenza vaccination in FMS patients. Nineteen FMS patients underwent physical and dolorimetric examinations and answered the fibromyalgia impact questionnaire (FIQ), the widespread pain index (WPI) checklist and the symptoms severity scale (SSS), which are part of the 2010 diagnostic criteria. Thirty-eight healthy subjects were recruited as controls. All participants were vaccinated with the inactivated split virion influenza vaccine. Serum was collected for antibody titration. Six weeks after vaccination, sera were tested by hemagglutination (HI) against A/California (H1N1), A/Perth (H3N2) and B/Brisbane. Humoral response was defined as either a fourfold or greater increase in titer, or an increase from a non-protective baseline level of <1/40 to a level of 1/40. No severe vaccination reactions were observed. No significant change was observed between WPI, SSS and FIQ values before and after vaccination, indicating no worsening of FMS symptoms. Vaccine immunogenicity: Six weeks after vaccination, FMS patients showed a significant increase in geometric mean titers of HI antibody. The rates of sero-protection increased from 22.9% for H1N1 to 89.5% post-vaccination. A significant increase in HI antibody titers was also demonstrated among healthy controls. Influenza vaccination was both safe and effective in FMS patients. In view of these results, FMS patients should be encouraged to undergo influenza vaccination according to the standard WHO recommendations.